Comprehensive Genomic Characterization of A Case of Granular Cell Tumor of the Posterior Pituitary Gland: A Case Report - Hong, Christopher S.; Elsamadicy, Aladine A.; Fisayo, Adeniyi; Inzucchi, Silvio E.; Gopal, Pallavi P.; Vining, Eugenia M.; Erson-Omay, E. Zeynep; Bulent Omay, Sacit (Frontiers in Endocrinology, 2021)
Granular cell tumors of the pituitary belong to a rare family of neoplasms, arising from the posterior pituitary gland. Although considered benign, they may cause significant morbidity and residual disease after resection can lead to poor clinical outcomes. Currently, there is no known medical therapy for any posterior pituitary gland tumor, in part due to sparse molecular characterization of these lesions. We report data from whole exome sequencing of a case of granular cell tumor of the pituitary, performed under an institutional review board approved protocol. A 77 year-old female underwent resection of an incidentally diagnosed pituitary mass that was causing radiographic compression of the optic nerves with a subclinical temporal field defect and central hypothyroidism. The pathology of the resected specimen demonstrated a granular cell tumor of the posterior pituitary gland. Whole-exome sequencing revealed mutations predicted to be deleterious in key oncogenes, SETD2 and PAX8, both of which have been described in other cancers and could potentially be amenable to targeted therapies with existing approved drugs, including immune checkpoint inhibitors and histone deacetylase inhibitors, respectively. To our knowledge, this is the first comprehensive genomic characterization of granular cell tumor of the posterior pituitary gland. We report mutations in oncogenes predicted to be deleterious and reported in other cancers with potential for therapeutic targeting with existing pharmacologic agents. These data provide new insights into the molecular pathogenesis of GCT of the pituitary and may warrant further investigation.